ANALISIS FUNGSI BADAN PERMUSYAWARATAN DESA DALAM PEMBANGUNAN DESA - Evi Hardiyanti Simamora; M. Arif Nasution; Agus Suriadi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2020)
In Law No. 6 of 2014 the village affirms that the village is no longer an administrative area, not even a subordinate or an element of regional implementation, but a special and independent area. The purpose of this research is to analyze the implementation of the function of Village Consultative Board in village development in Aloban Village, Portibi District, Padang Lawas Utara District. The method used in this study using descriptive method with a qualitative approach, research directed to provide accurate and systematic symptoms, facts or events about the properties of specific populations and areas. The results of this study found that the function of Village Deliberation Agency in Aloban Village has not been running as its function